Operational Excellence and Good Manufacturing Practices in Hospital Pharmacy - Wakhid Slamet Ciptono; Mulia Apriani Im (Universitas Trisakti, 2007)
This study focuses on building Operational Excellence OE) and current Good Manufacturing Practices (CGMP) for pharmaceuticals through 19 hospital pharmacy installations of Jogjakarta-and Central Java Provinces in lndonesia. Operational Excellence (OE) has an obsessive focus on efficiency and consistency in order to offer the better value of services. Current Good Manufacturing Practices (CCMP) is the regulations to assure that such drug meets the requirements of the act as to safety and has the identity and strength; and meets the quality and purity characteristics which it purports or is represented to possess. The study makes an attempt to provide and overview of the general status of the pharmacy installation provided by hospitals in the provinces of Jogjakarta and Centra Java in terms of their technical efficiency. The technical efficiency (TE) is analyzed using Data Envelopment Analisis (DEA). The motivation behind addressing the efficiency issue is to provide empirical analysis of continuos improvement and innovation policies which in turn provide hospital pharmacy services in both provinces.